THE INFLUENCE OF MANAGEMENT COMMITMENT, LEADERSHIP, EMPLOYEE ENGAGEMENT, AND TRAINING ON SAFETY PERFORMANCE AT A MANUFACTURING INDUSTRY IN BATAM - Agustinus Setyawan; Ferdinand Nainggolan; Asnil Fauzi (Journal of Business Studies and Management Review, 2021)
This study is aimed to analyze the influence of management commitment, leadership, employee involvement and training to safety performance. The samples were used by this study the employees who work in the manufacturing industry of Batam island. The method of data collection is conducted using questionnaire which distributed by google form to the companies. The sampling technique was used in this study is based on sampling of purposive. The amount of respondent is 138 questionnaires which distributed to three electronics manufacturing companies in the Muka Kuning of Batam island. The study shows that employee involvement and training considered siginificant a positive affect to the safety performance. But management commitment and leadership variables are not giving a significant effect to the safety performance.